Script Type Cooperative Learning Model on Student Learning Outcomes at Primary School - Olivya Haikutty; Domingus Rumalatu; Janes Pelamonia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Student academic success in IPAS, particularly regarding energy forms and their changes, is often sub-optimal when relying solely on traditional, one-way teaching methods that lack student engagement. This study aims to determine the effect of the Cooperative Script learning model on the learning outcomes of fourth-grade students at Primary School 71 Ambon. The research employed a quantitative quasi-experimental approach with a pretest-posttest control group design, where data were statistically analyzed using an independent sample t-test via IBM SPSS 27. The results revealed that the experimental group achieved a striking average post-test score of 20.88, significantly exceeding the control group’s average of 12.33. The t-test analysis yielded a significant value of 0.001 (p < 0.05), leading to the rejection of the null hypothesis (H_0) and the acceptance of the alternative hypothesis (H_a). Beyond cognitive improvement, the implementation of this model successfully transformed learning dynamics into a more active, enjoyable, and collaborative experience, fostering students' confidence and creativity through pair interactions. This study provides a practical contribution for elementary educators in implementing effective, innovative learning models and serves as a formal reference for developing interactive cooperative strategies in primary education.